Bangers : not only true tales from a 1960s teenage petrolhead, the cars, the girls, the dreams but also a girl's guide to silly old cars and the men obsessed by them /: not only true tales from a 1960s teenage petrolhead, the cars, the girls, the dreams but also a girl's guide to silly old cars and the men obsessed by them. ([2014?]) - Meade, Chris
No abstract available